Examining the Impact of Cancel Culture and Culture Wars on Social Media - Ardiyanto, Erik; Utami, Atika Budhi; Masful, Mila Falma (Communicare : Journal of Communication Studies, 2025)
Social media has become a significant platform for public communication, providing users with the freedom to express their opinions and engage in discussions. Through platforms like Twitter, individuals can easily access information and share their perspectives, leading to the rise of "Woke Culture" and, consequently, the emergence of "Cancel Culture." The term "cancel culture" refers to the act of publicly boycotting or shunning individuals or entities, particularly influencers and institutions, accused of violating societal norms or committing inappropriate actions. This phenomenon has been notably linked to allegations such as sexual harassment and ethical misconduct. Cancel culture operates within social media, where users mobilize to hold individuals accountable by condemning their actions. This research examines how cancel culture operates on social media platforms, particularly in Indonesia, and its impact on influencers and government institutions. Using a qualitative approach and critical discourse analysis, this study investigates the conversations and interactions surrounding cancel culture on social media. The findings reveal that while culture can foster social change and emancipation, it can also have divisive implications, fueling cultural conflicts and class antagonisms that contribute to the broader phenomenon of culture wars within society.